EVALUATION OF THE PERFORMANCE OF JAK LINGKO URBAN PUBLIC TRANSPORT ON ROUTES 1, 2, 3, 4, 5, 6, 7, 8, 9, AND 10 OF DKI JAKARTA PROVINCE - Ramadhanni, Muhammad Iqbal Fauzan; Murtedjo, Tedy; Chayati, Nurul (Universitas Ibn Khaldun Bogor, 2020)
Evaluation of the performance of urban public transport Jak Lingko on routes 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 provinces in Jakarta. DKI Jakarta is a city with all its activities that require transportation to support the movement of its people, whether in the city or people around the border with the city area. Existing public passenger transportation must have good performance or service. This research was conducted to see the performance and service level of Jak Lingko transportation in 2020. In total there are 53 routes that must be evaluated in the DKI Jakarta Province, but for this research that will be evaluated are routes 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10, if you have obtained the performance results of Jak Lingko public transport then based on the minimum service standard method (SPM) Decree of the Director General 2002 and the SPM of the World Bank. The results of the analysis of these 10 routes found 4 routes in 2 indicators that need to be improved again or that do not meet the SPM parameters, the routes in question are the Jak 9, Jak 4, Jak 6 and Jak 7 routes. The headway indicator which is in the middle parameter of SPM Decree of the Director General of 2002, in the travel indicator does not meet the World Bank SPM, 3 more routes namely Jak 4, Jak 6 and Jak 7 which need to be improved again are in the travel indicators for SPM SK Dirjen 2002.